The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/pathogens10111418
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Host Resistance to Tomato Spotted Wilt Orthotospovirus in Peanut Cultivars on Virus Population Genetics and Thrips Fitness

Abstract: Thrips-transmitted tomato spotted wilt orthotospovirus (TSWV) is a major constraint to peanut production in the southeastern United States. Peanut cultivars with resistance to TSWV have been widely used for over twenty years. Intensive usage of resistant cultivars has raised concerns about possible selection pressure against TSWV and a likelihood of resistance breakdown. Population genetics of TSWV isolates collected from cultivars with varying levels of TSWV resistance was investigated using five TSWV genes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…TSWV-induced phenotypes in this study could potentially be influenced by the different isolates (from field-collected foliage). Partial sequencing of TSWV isolates from the last 10 years, including the isolates used in this study, indicated a tremendous amount of variation in sequences in a given spatial scale [ 18 , 48 ]. However, purifying selection seems to be the major factor influencing the population genetics and evolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TSWV-induced phenotypes in this study could potentially be influenced by the different isolates (from field-collected foliage). Partial sequencing of TSWV isolates from the last 10 years, including the isolates used in this study, indicated a tremendous amount of variation in sequences in a given spatial scale [ 18 , 48 ]. However, purifying selection seems to be the major factor influencing the population genetics and evolution.…”
Section: Discussionmentioning
confidence: 99%
“…However, purifying selection seems to be the major factor influencing the population genetics and evolution. Also, isolate effects on the host phenotype were not influenced by host resistance to TSWV [ 18 , 48 ]. Despite using multiple isolates in this study, the phenotype induced by TSWV does not seem to be affected by host resistance in diploids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several examples of multigenic resistance and tolerance that provide long-term stable reductions in pathogen losses. One current example is a multigenic field resistance that appears to be providing long-term durable control of TSWV in peanuts [80]. Sequence-level population analysis of multiple TSWV genes did not detect any resistance-related selection in TSWV populations, indicating that this multigenic resistance is likely to be durable.…”
Section: Genetic Resistancementioning
confidence: 99%
“…The QTLs on A01 alone were responsible for 36% phenotypic variation associated with TSWV resistance, and A09 QTL contribution to TSWV resistance also was significant but not estimated ( Tseng et al., 2016 ; Agarwal et al., 2019 ). Unlike tomato and pepper wherein the selection pressure induced by TSWV has led to resistance-breaking variants, no such resistance-breaking variants have been documented in peanut thus far ( Sundaraj et al., 2014 ; Lai et al., 2021a ). Therefore, it is likely that TSWV resistance in peanut is governed by multiple genes.…”
Section: Introductionmentioning
confidence: 99%